MERGE: A Multinational, Multicenter Observational Registry for Myeloproliferative Neoplasms in Asia, including Middle East, Turkey, and Algeria. (30th April 2020) - Yassin, Mohamed A.; Taher, Ali; Mathews, Vikram; Hou, Hsin‐An; Shamsi, Tahir; Tuğlular, Tülin Firatli; Xiao, Zhijian; Kim, Soo‐Jeong; Depei, Wu; Li, Junmin; Rippin, Gerd; Sadek, Islam; et al.
Abstract: Philadelphia chromosome‐negative (Ph−) myeloproliferative neoplasms (MPNs) are a heterogeneous group of clonal disorders of the bone marrow, and are associated with a high disease burden, reduced quality of life (QOL), and shortened survival. This multinational, multicenter, non‐interventional registry "MERGE" was initiated with an objective to collect data on the epidemiological indices of classical Ph‐MPNs, existing treatment patterns, and impact of MPNs on health‐related QOL in various countries/regions in Asia, including the Middle East, Turkey, and Algeria. Of the 884 eligible patients with MPNs, 169 had myelofibrosis (MF), 301 had polycythemia vera (PV), 373 had essential thrombocythemia (ET), and 41 had unclassified MPNs. The median age was 58 years (range, 47‐66 years), and 50% of patients were males. The prevalence and incidence of MPNs were estimated to be 57‐81 and 12‐15 per 100 000 hospital patients per year over the last 4 years, respectively, in these countries. Total symptom score (mean [standard deviation; SD]) at baseline was highest in patients with MF (23.5 [17.47]) compared with patients with ET (14.6 [14.26]) and PV (16.6 [14.84]). Patients with ET had a lower mean (SD) number of inpatient visits (0.9 [0.77] days), and patients with MF had more outpatient visits (5.2 [3.17] days) on an average, compared with the entire MPN group. The study showed that patients with MPNs have a severe disease burden and reduced QOL. A discordance between physician and patient perception of symptom assessment was observed in this study (International clinical trials registry ID: CTRI/2014/05/004598). Abstract : This MERGE registry study provides epidemiological data on the distribution of MPNs and their diagnosis, management, and treatment patterns in developing emerging countries in Asia, including the Middle East, Turkey, and Algeria. The study showed that patients with MPNs have a severe disease burden and reduced quality of life. A discordance between physician and patient perception of symptom assessment was observed in this study.